Assim falava Adriano: uma análise das tramas do crime e da ordem - Silva, Paulo Henrique Rodrigues da (2023)
The research analyzes the recent social transformations observed in the plots of crime and order in Brazil, addressing issues related to the opposition between family life and life in crime, in understanding the aesthetics of existence considered marginal (GENET, 1986). In this sense, I analyze the life trajectory of Adriano Passos, who at first glance would be just a modest beach hut merchant. However, behind the scenes of his socially recognized businesses, which served as layers of concealment of his true practices, Adriano managed an extensive network of contacts and influences related to drug trafficking, being a cocaine supplier of considerable respect in the beach neighborhoods of the municipality of Caucaia (Ceará). I met Passos in 2009, when he later asked me to write a book about his life in crime. Thus, we established numerous dialogues that were more intense between 2012 and 2013. On these occasions Adriano narrated several experiences he had in São Paulo, where he was initially involved in bank robberies and was imprisoned for 10 years in Complexo do Carandiru, a place of great symbolic charge in the Brazilian imagination of State violence, racism and police lethality. Adriano stated that he heard the entire Massacre of October 2, 1992, which took place in Pavilion 9, which resulted in the death of hundreds of inmates and impacted the formation of numerous criminal factions, with emphasis on the Primeiro Comando da Capital (PCC) and the strengthening of the Comando Vermelho (CV). Despite having established intense dialogues with Adriano from 2009 to 2013, I was unable to carry out the research while he was still alive. In February 2016, I received the news that Adriano and his ex-wife, Eva, had been cruelly stabbed to death, which prompted me to rescue and analyze the intimate and collective plots surrounding the circumstances of their deaths. Covering physical and imaginative displacements, the work essentially consists of an investigation, analysis and interpretation of experiences, images, documents, interviews and police statements, seeking to highlight the hidden details of Adriano Passos' intense and complex criminal career and demonstrating the recent transformations in the plots of the crime and order in Brazil.